HPLC Method for Determination of Gliclazide in Human Serum - GHAI, DAMANJEET; LAKSHMI GANESH, GORLE (Asian Journal of Chemistry, 2010)
A simple, rapid and specific method for analysis of gliclazide in serum by a sensitive high-performance liquid chromatographic method is described. Only 100 μL of serum and a little sample work-up is required. A simple procedure of extraction by toluene followed by evaporation to dryness under a gentle stream of air and dissolving the dried residue in mobile phase was used. The gliclazide peak was separated from endogenous peaks on a C18 column by a mobile phase of acetonitrilemethanol- water (50:30:20, v/v), pH 3. Gliclazide and internal standard (phenytoin) were eluted at 4.85 and 3.8 min, respectively. The limit of quantification (LOQ) for gliclazide in serum was 50 ng/mL at 230 nm. The method was linear over the range of 50-10,000 ng/mL with r2 of 0.999. Mean recovery for gliclazide and internal standard was 85.5 and 86.0 %, respectively.